Secure decentralized internet of things infrastructure - Santos, Vasco Alexandre Maia dos (2017)
Despite many IoT Infrastructures having been implemented in recent years, none of them is truly prepared for a global deployment, where failure tolerance and scalability are an essential requirement. This dissertation presents an alternative concept for IoT Infrastructures, which focuses on enhancing the traditional centralized architecture, usually operated by a single entity, into a decentralized architecture featuring multiple entities and use cases. We propose a dynamic, community driven and self-configurable infrastructure on top of a structured Peer-to-Peer network, based on a Distributed Hash Table. Moreover, the proposed infrastructure is flexible enough to allow each peer of the overlay to enable a set of different services, according to its capabilities. In addition, a set of communication protocols is provided in order to support heterogeneous devices, as well as data access, streaming and persistence. It is also an important focus of our proposal to have mechanisms that guarantee the privacy and security of the information flow and storage.